Consequences for genetic diversity and population performance of introducing continental red deer into the northern distribution range - Haanes, Hallvard; Røed, Knut H; Mysterud, Atle; Langvatn, Rolf; Rosef, Olav (Conservation genetics, 2010)
For several centuries, game management has involved translocations of non-native individuals of many species to reinforce local native populations. However, there are few quantitative studies of potentially negative effects on population viability as expected when taxa with different local adaptations hybridise. The European red deer has been subject to particularly many translocations. Around 1900, a total of 17 red deer of Hungarian (Cervus elaphus hippelaphus) and German (C. e. germanicus) origin were introduced onto the island of Otterøya in Norway where few native red deer (C. e. atlanticus) remained (n ~ 13). To assess interbreeding, the present stock on Otterøya and the indigenous Norwegian and Hungarian populations were characterised in 14 microsatellite loci and in the control region of mtDNA. An intermediate level of genetic variation in the Otterøya population and the presence of population specific alleles from both the indigenous Norwegian and the Hungarian population demonstrate that the introduced red deer interbred with the native. Even distributions of one indigenous and one non-indigenous mtDNA haplotype in the Otterøya population and two point estimates of admixture indicate similar genetic contributions from the two parental populations into the hybrid stock. Low numbers of migrants identified with Bayesian assignment tests demonstrate low recent gene flow from Otterøya into the Norwegian mainland population. The Otterøya hybrid stock has grown vastly in numbers during recent decades, suggesting a high population viability. We observed that the body mass of red deer on Otterøya was similar or greater than in adjacent indigenous Norwegian stocks, indicating that population performance has not been reduced in the hybrid stock and that gene flow probably has not had any negative effects.